Sacred Symbols, Synthetic Lies: The Hijacking of Religious Authority in AI-Generated Religious Disinformation in Indonesia - Nuril Hidayah; Fitri Murfianti; Finsensius Yuli Purnama; Nur Fadhilah (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2026)
This study examines how generative artificial intelligence (AI) reshapes religious disinformation by disrupting the epistemological foundations of religious authority. Focusing on Indonesia and employing qualitative content analysis, the research analyzes AI-generated artifacts that simulate clerical voices, fabricate sacred symbols, and construct emotionally resonant narratives about the umma. Drawing on the framework of the epistemology of religious authority, the study explores how these artifacts challenge traditional mechanisms of verification, particularly within Islamic epistemology. This study contributes to the existing literature by demonstrating that AI not only disseminates misleading content but also reconfigures the ways in which religious truth is recognized. It does so by separating technical precision from moral accountability, producing sanad-less knowledge, and transforming sacred symbols into self-contained representations. While religious traditions possess epistemological tools such as isnād and tabayyun, their application becomes increasingly complex in AI-mediated environments where authority is no longer easily traceable. The study suggests that these tools remain relevant but require reinterpretation and adaptation. However, epistemological responses alone may be insufficient to address the affective dimension of AI-generated content, particularly regarding synthetic comfort.